2012
DOI: 10.1111/j.1475-097x.2012.01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular adaptations induced by 6 weeks WBV resistance exercise training

Abstract: To the best of our knowledge, this has been the first study to show that the superposition of vibration upon conventional resistance exercise does not have a specific effect upon long-term vascular adaptation in asymptomatic humans. Our findings seem to be at variance with the findings observed in a bed-rest setting. One possible explanation could be that the independently saturable effects of flow-mediated versus acceleration-related endothelial shear stresses on arterial structure and function differ between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Contrary to the purported mechanisms for exercise-training induced improvements in MBF (which include angiogenesis (Gavin et al 2007), capillarization (McCall et al 1996) and vascular remodelling of the arteriolar network (Weber et al 2013)), independent mechanisms must underlie the results observed in this acute intervention study as the compressed timeframe negates the possibility for the mechanisms outlined above. Based on the wellestablished improvements in endothelium dependent vasodilation afforded by the consumption of cocoa flavanols, possible mechanisms for this include altered: metabolite profiles (Schroeter et al 2006), cell signaling pathways, gene expression and/ or protein activity (Middleton et al 2000;Scalbert et al 2005), although our results suggest that this improvement is not linked to insulin signaling pathways as there were no differences in plasma insulin, proximal insulin signaling (AKT) or dextrose requirement to maintain a fixed blood glucose between the groups.…”
Section: Discussionmentioning
confidence: 74%
“…Contrary to the purported mechanisms for exercise-training induced improvements in MBF (which include angiogenesis (Gavin et al 2007), capillarization (McCall et al 1996) and vascular remodelling of the arteriolar network (Weber et al 2013)), independent mechanisms must underlie the results observed in this acute intervention study as the compressed timeframe negates the possibility for the mechanisms outlined above. Based on the wellestablished improvements in endothelium dependent vasodilation afforded by the consumption of cocoa flavanols, possible mechanisms for this include altered: metabolite profiles (Schroeter et al 2006), cell signaling pathways, gene expression and/ or protein activity (Middleton et al 2000;Scalbert et al 2005), although our results suggest that this improvement is not linked to insulin signaling pathways as there were no differences in plasma insulin, proximal insulin signaling (AKT) or dextrose requirement to maintain a fixed blood glucose between the groups.…”
Section: Discussionmentioning
confidence: 74%
“…Here, we have shown that 20 weeks of RET improved nutrient‐dependent increases in both LBF and muscle MBV in older men, independently of ‘acute’ exercise hyperaemia (measurements took place > 72 h after the last bout of RET). As exercise is known to induce angiogenesis (Gavin et al ., ), increases in muscle MBV are likely to result from increased capillarisation (McCall et al ., ) and vascular remodelling of the arteriolar network (Weber et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Using resistive exercise or resistive exercise with vibration, Weber and colleagues (Weber et al . ) reported no statistically significant changes in SFA, but observed a statistically significant 4.2% reduction in carotid artery wall thickness after 6 weeks. As discussed in that paper, Thijssen et al .…”
mentioning
confidence: 91%
“…We are not the first to report changes in carotid wall thickness but not SFA. Using resistive exercise or resistive exercise with vibration, Weber and colleagues (Weber et al 2013) reported no statistically significant changes in SFA, but observed a statistically significant 4.2% reduction in carotid artery wall thickness after 6 weeks. As discussed in that paper, Thijssen et al (2012) previously concluded that Letters J Physiol 595.11 high exercise intensities or high exercise volumes (or comparable cardiovascular haemodynamics) are required to affect carotid wall thickness.…”
mentioning
confidence: 98%